Dietary patterns and colorectal cancer recurrence and survival: a cohort study. Issue 2 (7th February 2013) - Zhu, Yun; Wu, Hao; Wang, Peizhong Peter; Savas, Sevtap; Woodrow, Jennifer; Wish, Tyler; Jin, Rong; Green, Roger; Woods, Michael; Roebothan, Barbara; Buehler, Sharon; Dicks, Elizabeth; et al.
Abstract : Objective: To examine the association between dietary patterns and colorectal cancer (CRC) survival. Design: Cohort study. Setting: A familial CRC registry in Newfoundland. Participants: 529 newly diagnosed CRC patients from Newfoundland. They were recruited from 1999 to 2003 and followed up until April 2010. Outcome measure: Participants reported their dietary intake using a food frequency questionnaire. Dietary patterns were identified with factor analysis. Multivariable Cox proportional hazards models were employed to estimate HR and 95% CI for association of dietary patterns with CRC recurrence and death from all causes, after controlling for covariates. Results: Disease-free survival (DFS) among CRC patients was significantly worsened among patients with a high processed meat dietary pattern (the highest vs the lowest quartile HR 1.82, 95% CI 1.07 to 3.09). No associations were observed with the prudent vegetable or the high-sugar patterns and DFS. The association between the processed meat pattern and DFS was restricted to patients diagnosed with colon cancer (the highest vs the lowest quartile: HR 2.29, 95% CI 1.19 to 4.40) whereas the relationship between overall survival (OS) and this pattern was observed among patients with colon cancer only (the highest vs the lowest quartile: HR 2.13, 95% CI 1.03 to 4.43). Potential effect modification was noted for sex (p value for interaction 0.04, HR 3.85 for women and 1.22 for men). Conclusions: The processed meat dietary pattern prior to diagnosis is associated with higher risk of tumour recurrence, metastasis and death among patients with CRC.